Development of Agropolitan Area in Papua (Case Study: Agropolitan Area in the City of Jayapura) - Sitorus, Yannice Luma Marnala; Yanthy , Normalia Ode; Nurmaningtyas, Anggia Riani (Asian Journal of Agriculture and Rural Development, 2015)
The agropolitan area in the eastern part of Indonesia to be not as developed as the western part of Indonesia. The city of Jayapura is an agropolitan area in the eastern part of Indonesia. This research was aimed at studying development of agropolitan area in the city of Jayapura. A qualitative approach with descriptive method was used to determine the superior potential of agricultural sector, to identify chain of production in agribusiness, and to identify service of infrastructure in each subsystem of agropolitan area. Contribution and rate of growth of agricultural sector towards GDP of the city of Jayapura decreased, Farmer Exchange Rate was under 100, decreased in micro loan of agricultural sector, and area of rice fields decreased, showing the stagnation of agropolitan area in that particular city. The superior products are rice, cash crops, vegetable, fruit, and livestock produce. Infrastructures on all agricultural subsystems are still limited and the most minimum is on subsystem infrastructure of downstream agribusiness. The majority of farmers there sell their produce directly to Youtefa market. Production chain is short thus it does not give much added value on the harvest. The local farmer group has a lack of critical attitude towards the existing development.